2012
DOI: 10.1371/journal.pone.0034241
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Phylogeography: A Targeted Approach for Multilocus Sequencing of Non-Model Organisms

Abstract: The field of phylogeography has long since realized the need and utility of incorporating nuclear DNA (nDNA) sequences into analyses. However, the use of nDNA sequence data, at the population level, has been hindered by technical laboratory difficulty, sequencing costs, and problematic analytical methods dealing with genotypic sequence data, especially in non-model organisms. Here, we present a method utilizing the 454 GS-FLX Titanium pyrosequencing platform with the capacity to simultaneously sequence two spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 44 publications
1
43
0
1
Order By: Relevance
“…The intron in Glucose-6-Phosphate Isomerase (GPI) was 324 bp long in each species, and sequenced in both the forward and reverse direction. The allelic state of heterozygotes were inferred by matching multiple peak chromatograms to alleles recovered from homozygous individuals, and this approach has been confirmed using next-gen sequencing [35]. All singleton alleles were confirmed by a second amplification and sequencing.…”
Section: Methodsmentioning
confidence: 89%
“…The intron in Glucose-6-Phosphate Isomerase (GPI) was 324 bp long in each species, and sequenced in both the forward and reverse direction. The allelic state of heterozygotes were inferred by matching multiple peak chromatograms to alleles recovered from homozygous individuals, and this approach has been confirmed using next-gen sequencing [35]. All singleton alleles were confirmed by a second amplification and sequencing.…”
Section: Methodsmentioning
confidence: 89%
“…In such cases, it is often unclear whether the lack of resolution is a result of power, methodological limitations, or a true lack of any population differentiation (Ryman et al 2006, Lowe and Allendorf 2010, Marko and Hart 2011; Table 2). The emerging field of high-throughput next-generation sequencing shows extreme promise in facilitating broader phylogeographic studies (e.g., Puritz et al 2012), the evolution of mating systems (e.g., Hart 2012), adaptation (e.g., Stapley et al 2010), and has been shown to resolve very recent divergence between marine and freshwater fish populations following an initial colonization event <150 yrs ago (Czesny et al 2012). In the Indo-Pacific region, next-generation sequencing has had a number of interesting applications and an exciting future; this is reviewed in more detail by Willette et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of massively parallel "next generation" sequencing it is now possible to generate genomic data and assess phylogeography on scales never before considered (e.g., Puritz et al 2012a). We can now survey entire nuclear, mitochondrial, and chloroplast genomes, and even the expression of genomes (Carstens et al 2012).…”
Section: A Brief Historymentioning
confidence: 99%